Estudo eletroquímico do sistema microestruturado montmorilonita-8- hidroxiquinolina na presença de íons metálicos - Lupi, Caroline Polini [UNESP] (2014)
Scientific progress has affected human life and nature, especially with regard to health and the environment. Particularly the presence of metal ions in the environment is responsible for the contamination of drinking water sources and its living organisms in these media, representing a great risk to humanity. The clay minerals are potentially retaining these ions. Thus, the clays have been object of attention for presenting technical and economic feasibility because of its potential for adsorption and reuse. The present work aimed to study the electrochemical behavior of microstructured systems, modified by employing the montmorillonite clay and the organic molecule, 8-hydroxyquinoline, considering their ability in a number of complexing metal ions. For this a platinum electrode was modified with a slurry of montmorillonite-8-hydroxyquinoline. The electrochemical stability of the modified electrode was confirmed by cyclic voltammetry, and studied the effect of addition of Cu (II) and Fe (III) to the system. The electrochemical behavior of the modified electrode in the presence of Cu (II) showed a pair of peaks at low ion concentrations, which were identified as belonging to a process of the EC type where initially there was the formation of a ternary complex ion with the metallic film clay-binder covering the surface of the electrode, the type {Pt / [> Si - O]n [Cu (II) - (8HQ)k]} 2-nk, then there was a reduction of ions Cu (II) to Cu (I) into the complex. For higher concentrations of Cu (II) modified electrode showed a pair of peaks in addition to the aforementioned two peaks in the anodic branch, which were established as being derived from the low adsorption of Cu (II) on the film covering the ternary complex the electrode surface. The electrochemical behavior of the modified electrode in the presence of Fe (III) showed the presence of four peaks interdependent. These peaks were identified as belonging to two different mechanisms: ...